Hand washing knowledge and practice among school going children in Duwakot, Bhaktapur: A cross sectional study - Manandhar, Pratibha; Chandyo, Ram Krishna (Journal of Kathmandu Medical College, 2018)
Background: Diarrhea and acute respiratory tract infection are the commonest cause of morbidity and mortality in Nepal. Proper hand washing techniques help to reduce the incidence of diarrhea and acute respiratory infection in children.Objective: Objective of this study was to identify hand washing knowledge and practice among school children of Duwakot, Bhaktapur.Methodology: This was a cross-sectional study conducted among 340 students of grade V, VI and VII from both the government and private schools of Duwakot, Bhaktapur. Convenient sampling technique was applied in government schools (due to less number of students) whereas students were randomly selected from private school (due to large number).Result: All the students had knowledge about the hand washing technique before meal and after defecation. Almost all (99.4%) students reported that they wash hand before meal and 92.4% students reported that they practiced hand washing after defecation. But, only 8.5% students at school and 47% students at home regularly washed hand with soap and water. However 91.6% students at school and 81% students at home washed hand only by water due to unavailability of soap.Conclusion: Although students had hand washing knowledge; proper hand washing practices was lagging behind.